Bridging the gap between exposure assessment and inhalation toxicology: Some insights from the carbon nanotube experience. (September 2016) - Erdely, Aaron; Dahm, Matthew M.; Schubauer-Berigan, Mary K.; Chen, Bean T.; Antonini, James M.; Hoover, Mark D.
Abstract: The early incorporation of exposure assessment can be invaluable to help design, prioritize, and interpret toxicological studies or outcomes. The sum total of the exposure assessment findings combined with preliminary toxicology results allows for exposure-informed toxicological study design and the findings can then be integrated, together with available epidemiologic data, to provide health effect relevance. With regard to engineered nanomaterial inhalation toxicology in particular, a single type of material (e.g. carbon nanotube, graphene) can have a vast array of physicochemical characteristics resulting in the potential for varying toxicities. To compound the matter, the methodologies necessary to establish a material adequate for in vivo exposure testing raises questions on the applicability of the outcomes. From insights gained from evaluating carbon nanotubes, we recommend the following integrated approach involving exposure-informed hazard assessment and hazard-informed exposure assessment especially for materials as diverse as engineered nanomaterials: 1) market-informed identification of potential hazards and potentially exposed populations, 2) initial toxicity screening to drive prioritized assessments of exposure, 3) development of exposure assessment-informed chronic and sub-chronic in vivo studies, and 4) conduct of exposure- and hazard-informed epidemiological studies. Highlights: Knowledge-of-exposure and knowledge-of-hazard influence the relevance and reliability of risk assessments. For engineered nanomaterials specifically, detailed exposure assessments are essential to development of toxicity findings that are relevant to human health. A framework is provided to better integrate exposure and toxicology assessments.